Including Employees With Disabilities in Workplace Cultures: Strategies and Barriers. (July 2015) - Hagner, David; Dague, Bryan; Phillips, Kimberly
Assisting individuals with disabilities to become socially included in the workplace is an important rehabilitation goal. This article reports the results of a descriptive study of the workplace cultures where individuals with disabilities are employed, the inclusion of employees within those cultures, the strategies used by employment specialists to promote inclusion, and the barriers encountered in the process. Fifty-three employment specialists who had successfully completed online training on analyzing workplace cultures and planning support strategies selected an individual they provided support to and completed an assessment instrument during the course of their visits to and contacts with the workplace. The distribution of workplace culture strength was bimodal, comprising a larger group with weaker cultures and a smaller group with stronger cultures. Individuals with disabilities were included in a mean of 83% of their workplace cultures. Employment specialists reported about twice as many barriers as strategies, indicating that they viewed most inclusion difficulties as beyond their role and function. The implications of these findings for job placement and support services are discussed.